The elements that influence sustainable consumption behaviour: the empirical analysis of electric vehicle consumption - Zhang, Qian (2022)
In recent years, the rapid development of the economy is bringing negative influences on environmental pollution and ecological imbalance, how to solve this contradiction has become the global issue commonly concerned. Sustainable consumption is a new pattern of consumption, which is conducive to environmental protection and reducing energy consumption. This study discusses sustainable consumption behaviour and affecting factors, with the purpose of finding the elements that influence sustainable consumption behaviour so that help decision-makers to encourage sustainable consumption behaviour . This research takes electric vehicles as an example for an empirical study on the influencing factors of consumers' sustainable consumption behaviour. Four hypotheses and constructs an analysis model based on the theory of planned behaviour and structural equation model is being put forward. The result shows that attitude, subjective norm, perceived behaviour control, and behavioural intention have positive effects on the occurrence of sustainable consumption behaviour. The prediction effect of consumption attitude is lower than other factors, and the influence of subjective norm is the strongest. In addition, there are several limitations to this study. This research also proposes future research, including the expansion of the theoretical model, the application constraint of the model, and the authenticity of the questionnaire survey.